2020
DOI: 10.1161/jaha.119.013359
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Biomarker Is Associated With Hospitalization and Mortality Among Heart Failure Patients

Abstract: Background The purpose of this article is to evaluate the association of voice signal analysis with adverse outcome among patients with congestive heart failure ( CHF ). Methods and Results The study cohort included 10 583 patients who were registered to a call center of patients who had chronic conditions including CHF in Israel between 2013 and 2018. A total of 223 acoustic features were extracted from 20 s of spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 21 publications
1
25
0
5
Order By: Relevance
“…Unstable pitch and loudness were observed in patients with multiple sclerosis 3 . Other recent studies also demonstrated distinct voice characteristics that were associated with various pathological, neurological, and psychiatric disorders, such as congestive heart failure 4 , Parkinson’s disease 5 , Alzheimer’s disease 6 , post-traumatic stress disorder 7 , and autism spectrum disorder 8 . The human voice is now considered as an emerging biomarker, which is inherently non-invasive, low-cost, accessible, and easy to monitor health conditions in various real-life settings.…”
Section: Introductionmentioning
confidence: 88%
“…Unstable pitch and loudness were observed in patients with multiple sclerosis 3 . Other recent studies also demonstrated distinct voice characteristics that were associated with various pathological, neurological, and psychiatric disorders, such as congestive heart failure 4 , Parkinson’s disease 5 , Alzheimer’s disease 6 , post-traumatic stress disorder 7 , and autism spectrum disorder 8 . The human voice is now considered as an emerging biomarker, which is inherently non-invasive, low-cost, accessible, and easy to monitor health conditions in various real-life settings.…”
Section: Introductionmentioning
confidence: 88%
“…The measurement of vocal biomarkers shows a good correlation with the degree of pulmonary hypertension [ 142 ]. In patients with heart failure, vocal biomarkers correlate with heart failure hospitalizations and mortality [ 143 ]. In a proof-of-concept study, AI was able to ensure the contactless detection of cardiovascular arrests using smart speakers or smartphones and differentiate between agonal breathing and hypopnea, central apnea and obstructive apnea [ 144 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Remote monitoring from wearable biosensors and mHealth is being investigated to improve outcomes in heart rhythm and heart failure and other cardiovascular conditions (44,(46)(47)(48)(49)(50), and may have utility for COVID-19 (19,(52)(53)(54)(55)(56)(57)(58) and Cardio-Oncology (59)(60)(61). Voice apps and voice analysis have shown promise in cardiology for heart failure, ischemic heart disease, pulmonary hypertension, and other forms of cardiovascular disease (45,(62)(63)(64), as well as cardio-oncology (65), and have been considered for COVID-19. Drones built on artificial intelligence are being used to deliver healthcare equipment, medicines, personal protective equipment, and food, especially to remote areas with high rates of illness with COVID-19, and are also being dispatched to dense urban locations to urge pedestrians to maintain social distancing (66)(67)(68).…”
Section: Innovation Beyond the Pandemic Artificial Intelligencementioning
confidence: 99%